Relationship between the small cervical vertebral body and the morbidity of cervical spondylosis. Issue 31 (August 2017) - Lu, Xin; Tian, Ye; Wang, Shu-Jie; Zhai, Ji-Liang; Zhuang, Qian-Yu; Cai, Si-Yi; Qian, Jun
Abstract : Abstract: This study aimed to determine the relationship between the size of the cervical vertebral body and the morbidity of cervical spondylosis, and to examine the characteristics of spondylosis patients with small cervical vertebral bodies. The clinical data and the sagittal reconstructions of computed tomography images of 182 patients with cervical spondylosis were collected retrospectively. Patients included 74 males and 108 females, with a mean age of 31.8 years (range 20–40 years). The Torg–Pavlov ratio and the sagittal diameter of the vertebral body were measured. A Torg–Pavlov ratio above 1.2 was regarded as a small cervical vertebral body (SCVB), and below 1.2 as a nonsmall vertebral body (NSCVB). The NSCVB group was more prone to neurological symptoms than was the SCVB group ( P  < .05). There was no significant difference in neck pain between the 2 groups ( P  > .05). Conservative treatment achieved similar recovery rates in the SCVB group and the NSCVB group (81.8% vs 93.6%; P  > .05). The rate of symptom (eg, axial neck pain) recurrence and persistence in the SCVB group was significantly higher than in the NSCVB group ( P  < .05). Our study found that smaller size of the cervical vertebral body is an attributing factor for cervical spondylosis. Patients with smaller cervical vertebral bodies are prone to persistent axial neck pain, but not neurological symptoms.